Assessment Of Caesarean Section Rates Using Robson Ten Group Classification System In Vmkv Medical College And Hospital - R Pillai, Remya; B. Jeyamani, B. Jeyamani; Priya, G. Prema; R Pillai, Remya (Journal of Neonatal Surgery, 2025)
Background and Objectives: Caesarean section (CS) is a crucial surgical intervention for maternal and fetal well-being when medically indicated. However, its rising global trend has become a public health concern. The World Health Organization (WHO) has recommended that CS rates should not exceed 15%. The Robson Ten Group Classification System (RTGCS) serves as an effective tool for analyzing CS rates and implementing measures to reduce unnecessary procedures. This study aims to assess the CS rate in VMKV Medical College and Hospital using the RTGCS and identify contributing factors. Methods: This cross-sectional, hospital-based observational study was conducted in the Department of Obstetrics and Gynecology at VMKV Medical College and Hospital over 1.5 years (November 2022 to May 2024). A total of 500 pregnant women who delivered via normal vaginal delivery (NVD) or CS were classified into ten groups based on RTGCS. Data analysis was performed using SPSS v16, with qualitative variables expressed in frequencies and percentages and quantitative variables in mean and standard deviation. Statistical significance was set at p<0.05. Results: The majority of deliveries occurred in the 21-25 age group (51.8%), followed by 26-30 years (36.8%). CS rate was 32.2%, with the highest contribution from Group 5 (previous CS, single cephalic, ≥37 weeks) at 48.4%. Maternal outcomes were predominantly good (97.8%), with postpartum hemorrhage (PPH) observed in 2.2% of cases. Fetal complications were minimal, with transient tachypnea of the newborn (TTN) at 1.19%, meconium-stained liquor (MSL) at 0.79%, and respiratory distress syndrome (RDS) at 0.6%. Conclusion: The study highlights an increasing trend in CS, primarily due to repeat cesarean deliveries (Group 5). The Robson classification provides an effective means to monitor and evaluate CS trends. Implementing targeted strategies to reduce unnecessary CS procedures, especially in low-risk pregnancies, can help optimize maternal and neonatal outcomes.